Geometria Figurativa - Nickas, Bob (Milano : Silvana Editoriale Spa, 2017)
Benning, Sadie ; Brown, Alex ; Holst, Mamie ; Hughes, Chip ; Jane, Xylor ; Janitz, Robert ; Müller, Ulrike ; Roggy, Nicolas ; Tinkler, Richard
Geometria Figurativa, Collezione Maramotti, Reggio Emilia, 16.10.2016 - 02.04.2017
boek